1990
DOI: 10.1007/bf01782984
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up on a 1962 case-control study of trace elements as risk factors for stomach cancer in Iceland

Abstract: In 1988 a follow-up investigation was made of a case-control study conducted in 1962 in Iceland which tested hypotheses that trace elements in pasture grass, drinking water and cow's milk were associated through diet with cancer of the stomach. Samples were collected in 1962 from 26 farms in the northern county of Skagafjardarsysla and 30 farms in the southern county of Rangarvallasysla. The main objective of the present study was to establish the cancer experience of the 297 residents of the 56 farms since 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In the county of Rangarvallasysla in Iceland, boron deficiency in pasture grass, drinking water and cow's milk was associated with cancer of the stomach (Armstrong, 1990). Based on a study of 76 cases and 7751 controls, low dietary boron intake was associated with increased prostrate cancer risk (Zhang et aI., 2001).…”
Section: Boron Effects On Cancer Incidence and Preventionmentioning
confidence: 97%
“…In the county of Rangarvallasysla in Iceland, boron deficiency in pasture grass, drinking water and cow's milk was associated with cancer of the stomach (Armstrong, 1990). Based on a study of 76 cases and 7751 controls, low dietary boron intake was associated with increased prostrate cancer risk (Zhang et aI., 2001).…”
Section: Boron Effects On Cancer Incidence and Preventionmentioning
confidence: 97%
“…For example, Piispanen (1989) compared cancer and geochemical maps of Finland but found only weak associations. When Armstrong (1990) revisited an earlier study area in Iceland he concluded that the pronounced geographical variation in Icelandic stomach cancer incidence that was widely cited from 1961 to 1965 is now believed to be spurious. Multiple sclerosis is a relatively uncommon disease which is very difficult to diagnose in its early stages.…”
Section: Introductionmentioning
confidence: 94%